2010
DOI: 10.3724/sp.j.1235.2010.00111
|View full text |Cite
|
Sign up to set email alerts
|

Clays in radioactive waste disposal

Abstract: International audienceClays and argillites are considered in some countries as possible host rocks for nuclear waste disposal at great depth. The use of compacted swelling clays as engineered barriers is also considered within the framework of the multi-barrier concept. In relation to these concepts, various research programs have been conducted to assess the thermo-hydro-mechanical properties of radioactive waste disposal at great depth. After introducing the concepts of waste isolation developed in Belgium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 30 publications
2
83
0
Order By: Relevance
“…An important thermally-induced effect in low permeability media such as clays and claystones is the pore water pressurization that occurs upon heating (Delage et al 2010;Mohajerani et al 2012). Such strong THM couplings were clearly demonstrated from both in situ experiments and laboratory tests performed in the TIMODAZ project.…”
Section: Strong Thermo-hydro-mechanical Couplingmentioning
confidence: 85%
See 2 more Smart Citations
“…An important thermally-induced effect in low permeability media such as clays and claystones is the pore water pressurization that occurs upon heating (Delage et al 2010;Mohajerani et al 2012). Such strong THM couplings were clearly demonstrated from both in situ experiments and laboratory tests performed in the TIMODAZ project.…”
Section: Strong Thermo-hydro-mechanical Couplingmentioning
confidence: 85%
“…However, an increase of intrinsic permeability from -19 m² to 2×10 -16 m² was observed in one drained shearing test on the Boom Clay performed at Laboratoire 3SR in Grenoble (Delage 2010). According to Viggiani and Bésuelle (2012), this can be explained by the reopening of pre-existing cracks under a low mean stress (p'=0.3 MPa).…”
Section: Safety-relevant Aspects Of Thm Perturbation and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main component used for EBS is very low permeable Bentonite clay to limit any advection transfer (Delage et al, 2010;Bianchi et al, 2014). In this real situation, if the radionuclide transport occurs or engineering barrier layer fails, initially it transports through low hydraulic conductivity medium of bentonite clay (diffusion dominated) and it enters to the GBS later onwards gradually it enters to the geological medium (advection dominated) (Bianchi et al, 2014).…”
Section: Application Problemmentioning
confidence: 99%
“…The hydraulic conductivity and dispersion coefficient of each medium varies drastically from one layer to another. The seepage velocity and dispersion coefficient for EBS, geological barrier and geological medium are adopted from previous studies which have shown in Table 2 (Delage et al, 2010;Yi et al, 2012). The peclet Number (Pe) of EBS and geological media were calculated using equation, Pe = by applying adopted hydrological parameters.…”
Section: Application Problemmentioning
confidence: 99%